(untitled) (Dhaka University Journal of Science, 2024)
The composition and stability constant of the complexes of copper(II) with the ligands 2,2 –bipyridine, 1,10-phenanthroline, saccharin, and ethylenediamine tetraacetic acid (EDTA),were determined, as well as the effect of temperature on the thermodynamic parameters were studied. The metal-to-ligand ratio in the EDTA complex is found 1:1 and in the rest of the cases, the ratio is 1:2. The redox behavior of the Cu (II) / Cu (0) system in the Cu-ligand complex has been studied in KCl solution as a supporting electrolyte. The redox process of the Cu (II) / Cu (0) system in the Cu-sac complex is almost similar to that of the Cu (II) solution in the absence of any ligand. In other cases, the redox process is a single-step 2-electron transfer process. The electron transfer process in all the cases is diffusion-controlled. The values of peak current ratio and peak potential separation are the evidence that the redox processes are quasi-reversible. Dhaka Univ. J. Sci. 72(2): 61-67, 2024 (July)